A novel chemical lysis method for maximum release of DNA from difficult-to-lyse bacteria. (January 2019) - de Bruin, Olle M.; Chiefari, Amy; Wroblewski, Danielle; Egan, Christina; Kelly-Cirino, Cassandra D.
Abstract: Molecular detection of microorganisms requires releasing DNA from cells. However, since certain microbial organisms are refractory to lysis by chemical or enzymatic methods, mechanical lysis by bead-beating is typically employed to disrupt difficult-to-lyse microbes. A newly developed chemical lysis method called sporeLYSE enables release of DNA from difficult-to-lyse microbes without bead-beating. The sporeLYSE method was compared to bead-beating and an alkaline/detergent lysis solution for releasing DNA from microbes grown in vitro, including surrogates of Category A bioterrorism agents. sporeLYSE released 83% to 100% of DNA from Mycobacterium smegmatis, Francisella philomiragia, Yersinia enterocolitica, Bacillus thuringiensis, Pseudomonas aeruginosa, Moraxella catarrhalis and Klebsiella pneumoniae. qPCR results indicated that sporeLYSE extracted an equal or greater amount of DNA than either bead-beating or alkaline/detergent lysis from Gram-positive and Gram-negative bacteria. When sporeLYSE was used to extract DNA from saliva and sputum spiked with M. smegmatis and M. tuberculosis, respectively, the qPCR Ct values were 4–8 cycles lower than those for extractions via alkaline/detergent lysis and heat. Mean Ct values for sporesLYSE extractions from spores of Clostridium difficile and C. botulinum were approximately two cycles lower than those of MagNA Pure DNA extractions. Our results suggest that sporeLYSE is an easy-to-use liquid reagent that can efficiently release large amounts of DNA from a variety of bacteria, including spores. Graphical abstract: Highlights: sporeLYSE is a highly efficient, liquid reagent for bacterial DNA extraction. Suitable for extracting DNA from difficult-to-lyse bacteria, including spores. Simplifies DNA extraction protocols by eliminating the need for bead-beating. Suitable for extracting DNA from bacteria in biological samples.